The Regulatory Authorities’ Role in Enforcing Laws on Misleading Cosmetic Claims in Indonesia and European Union - Ugra Abhiseka, Dewa Ngakan; Mahadewi, Kadek Julia (JURNAL AKTA, 2025)
The rapid growth of Indonesia’s cosmetics industry has led to a rise in misleading product claims that pose risks to consumers and weaken legal protections. This study examines the role of regulatory authorities in enforcing laws against misleading cosmetic claims in Indonesia and compares these mechanisms with those of the European Union to identify structural, procedural, and substantive gaps that influence enforcement effectiveness. Using a normative legal research method combined with a comparative approach, the study analyzes relevant legislation, official regulatory documents, and judicial decisions. The findings show that although Indonesia has a solid legal foundation through the Consumer Protection Act and the Health Law, supported by both pre-market and post-market surveillance, enforcement remains significantly weaker than in the European Union. Key factors include the absence of detailed claim-assessment standards equivalent to the EU’s Common Criteria, limited authority of BPOM in pursuing criminal actions, and a reactive, case-by-case enforcement model. Conversely, the European Union employs a preventive and systematic framework characterized by rigorous claim verification, standardized scientific substantiation, and broad supervisory powers. This study concludes that Indonesia’s challenges stem not from inadequate legal norms but from insufficient technical standards and institutional capacity. The research offers novelty by highlighting the institutional and technical gaps that hinder Indonesia’s enforcement of misleading cosmetic claims and by providing recommendations for strengthening national regulatory mechanisms to align with international consumer protection standards.